A proposal of knowledge engineering metrics - Britos, Paola Verónica (2005)
Metrics used on development of expert systems is not a well investigated problem area. This article suggests some metrics to be used to measure the maturity of the conceptualization process and the complexity of the decision process in the problem domain. We propose some further work to be done with these metrics. Applying those metrics makes new and interesting problems, concerning the structure of knowledge to surface.